The Interplay of Social Media Marketing Activities, Customer Involvement, and Repurchase Intention in Public Transportation Services - Pantjolo Giningroem, Dewi Sri Woelandari; Roosdhani, Mohamad Rifqy; Komaryatin, Nurul; Putra PR, M Rivi (JOURNAL OF ADVANCED STUDIES IN MANAGEMENT, 2024)
This study explores the influence of social media marketing activities on customer engagement and repurchase intentions in the context of PO Bejeu Jepara's bus transportation services. Using quantitative methods, data was collected through in-person interviews and online surveys with 210 respondents. The analysis was conducted using the Structural Equation Modeling (SEM) method with SmartPLS version 4.0 software. The results showed that social media marketing activities have a positive and significant influence on customer engagement, which in turn increases repurchase intentions. However, the direct effect of social media marketing activities on repurchase intentions was found to be negative and insignificant, suggesting partial mediation by customer engagement. These findings underscore the importance of increasing customer engagement through quality social media content to drive brand loyalty and repeat purchases. This research contributes to the literature by highlighting the mediating role of engagement in the relationship between social media marketing activities and repurchase intentions, and provides practical insights for companies to strengthen their marketing strategies on social media.